2018
DOI: 10.3892/ol.2018.9600
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin in inducing apoptosis of bladder cancer cells through inhibiting SIRT1/p53 pathway

Abstract: Regulatory effect of puerarin on bladder cancer T24-cell apoptosis and its possible mechanism were investigated. The experimental subjects were divided into the experimental group, the control group and the blank control group, and the cell inhibition rates after treatment were detected, respectively. Then, subjects were further divided into the control group, the puerarin group (treated with puerarin), the agonist group [treated with silent information regulator 1 (SIRT1) agonist SRT1720], the inhibitor group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…A study shows that SIRT1 enhances the metabolic flexibility [41]. Moreover, SIRT1 promotes glucose transporting [42] and inhibits apoptosis of cancer cells [43]. Our present results are consistent with these reports.…”
Section: Discussionsupporting
confidence: 93%
“…A study shows that SIRT1 enhances the metabolic flexibility [41]. Moreover, SIRT1 promotes glucose transporting [42] and inhibits apoptosis of cancer cells [43]. Our present results are consistent with these reports.…”
Section: Discussionsupporting
confidence: 93%
“…To date, many natural occurring products have drawn extensive attention as anticancer agents in the management of cancer development, because of their potential tumor selectivity and low cytotoxicity [11]. Puerarin (PEU), a much famous isoflavone-C-glycoside, is the principal bioactive ingredient from the traditional Chinese herb Radix puerariae, which owns a wide range of biological activities, including cardioprotection, neuroprotection, anti-inflammatory, antioxidant, alleviating pain, inhibiting alcohol intake, regulation of bone metabolism and reduction of intraocular pressure [12][13][14]. Furthermore, an increasing body of evidence has demonstrated PEU also showed anticancer effects in a variety of cancer cell lines, such as lung cancer [15], cervical cancer [16], esophageal cancer [17], bladder cancer [18], gastric cancer [19], colon cancer [20], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the majority of drugs exert their anti-cancer effects via inducing apoptosis of tumor cells. 28,30,31 In addition, Zhang et al 32 revealed that bortezomib triggered cell apoptosis in cervical cancer cells. Bruning et al 23 further reported that bortezomib also triggered apoptosis in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%